Coaches' beliefs about shy children and adolescents in the context of team sports - Nguyen, K.; Coplan, R. J.; Archbell, K. A.; Rose-Krasnor, L. (International Sport Coaching Journal, 2021)
The goal of this study was to explore coaches` beliefs about the role of child and adolescent shyness in team sports. Participants were (N = 496) coaches of children and adolescents from team sport organizations across Canada. Coaches responded to open-ended questions asking about the benefits of team sports participation for shy children and adolescents, as well as the special contributions that shy team members may make to a sports team. Among the results, coaches cited improvements in social skills most often as the primary benefits of engaging in team sports for shy team members. Coaches most frequently listed promoting social inclusion, quiet leadership, and being coachable as specific contributions of shy team members. Some age differences were also noted. Results are discussed in terms of implications of shyness for children and adolescents who participate in organized team sports.